FAIRNESS PERCEPTIONS AS A MODERATOR IN THE CURVILINEAR RELATIONSHIPS BETWEEN JOB DEMANDS, AND JOB PERFORMANCE AND JOB SATISFACTION. - Janssen, O. (Academy of Management Journal, 2001)
Activation theory suggests that intermediate rather than low or high levels of quantitative job demands benefit job performance and job satisfaction among managers. Using an equity theory framework, I hypothesize that perceptions of effort-reward fairness moderate these inverted U-shaped demand-response relationships. In support of this hypothesis, survey results demonstrate that managers who perceive effort-reward fairness perform better and feel more satisfied in response to intermediate levels of job demands than managers who perceive "underreward unfairness."